Evaluation of the Leprosy Program Implementation at Teminabuan Health Center, South Sorong District, Using the CIPP Evaluation Model - Onim, Florence; Uly, Nilawati; Al-Maidin, Achmad R. Muttaqien; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Leprosy is a chronic infectious disease that poses significant challenges and impacts family well-being. In 2023, 75 cases were recorded and treated in South Sorong. Objective: This study aimed to evaluate the implementation of the leprosy program at Teminabuan Health Center using the CIPP (Context, Input, Process, Product) evaluation model. Methods: A descriptive qualitative approach was applied, using observation and in-depth interviews with three key informants. Data validation was conducted through triangulation. Results: Context evaluation showed collaboration between health workers and community cadres in raising awareness and promoting early examination. Input evaluation revealed program management by a designated officer with support from several units but highlighted issues such as limited staff, lack of integrated data systems, and insufficient drug supply. Process evaluation indicated that outreach was done through leaflets and discussions, field screening, and referrals, though stigma and behavior change remained challenges. Product evaluation found that activities included contact tracing, medication monitoring, and referrals, but training for health workers was inadequate. Conclusion: While context and process aspects were satisfactory, input and product components need improvement, particularly in human resources, logistics, and system integration to enhance program effectiveness